Gjergj Kastrioti – Skanderbeg between Literature and Historiography - Kamberi, Kamber; Berisha, Labinot (Technium Social Sciences Journal, 2023)
The figure of Gjergj Kastrioti-Skanderbeg has aroused interest from an early age in historiographers, writers, creators of other arts, but also in military doctrines. With his feats, he drew the attention of various circles and institutions in many countries of the world. The beginnings of the treatment are from the glorious period of 25 years of heroic resistance against the Ottoman Empire, and it is especially emphasized, after his death. The creations are among the most diverse and come from different countries, which means that his heroism had crossed his national horizon. His relationship with the three popes and the proclamation "Athleta Christi" (Champion of Christ) prove his importance and the role he played in the course of his people’s history, but also beyond. Also, alliances and coalitions with various European countries for the protection of lands, ethnicity and Western culture make this creativity very rich. Therefore, to approach this corpus for a summarized, perhaps superficial study, a great commitment is required and a selection that does not mean that it is the best. However, in this approach, multiple study methods are required or present, such as deductive, inductive, synthesizing, analytical, historical, comparative, etc. All these are in function to present a reasoned approach with a conclusion based on factual works. Since the volume of this topic is quite wide, a comprehensive approach was impossible, which means that the presentation in this paper is not comprehensive and exhaustive.